Gut Reaction: The Impact of a Film on Public Understanding of Gastrointestinal Conditions - Gomes, Diogo; Loth, Alina; Hockley, James R. F.; Smith, Ewan St. John (Frontiers in Communication, 2022)
Chronic gastrointestinal (GI) tract conditions are common conditions associated with disordered bowel movements and significant pain. However, discussion of bowel habits is often regarded as taboo and public understanding of what exactly these conditions are, and how they impact the lives of those individuals with such conditions is poorly understood. To provide a platform for enhancing public engagement of chronic bowel conditions, a short film was made (Gut Reaction) examining the lives of four individuals with different bowel conditions and what scientists and clinicians are doing to help alleviate the pain experienced by such individuals. This film was then screened at a science festival where a pre- and post-film survey was conducted alongside follow up semi-structured interviews with a small subset of those who had expressed willingness to engage in such an interview. Although films have been used for public engagement and health campaigns, there is a lack of a robust evaluation of such methods. As such, there is no knowledge of impacts and outcomes, jeopardising funding of such projects. Overall, the pre- and post-film surveys demonstrated that the film had increased the attendees’ understanding of chronic bowel conditions, how they are treated, what research is on-going and the likelihood of discussing bowel conditions with friends and family. The follow-up interviews were analysed through the constant comparative coding process. The analysis revealed that participants have a strong belief that bowel conditions need to be part of normal conversations, and the understanding of such conditions, and the people who experience them, needs to be improved by society. Our participants hold that this is crucial for people who experience from such conditions, not least to be able to access help sooner and suffer less. Finally, our participants discussed two strategies to achieve this societal openness and tackle the sense of shame around these issues: one involving role models and the other the media. In summary, Gut Reaction appeared to have met its objectives of improving the viewers' awareness and understanding of chronic bowel conditions, as well as removing some of the stigma and taboo that surround discussions about these conditions.